Ethnic differences in parental experiences during the first six months after PICU discharge in Singapore: a qualitative study - Poh, Pei-Fen; Carey, Matthew C.; Manning, Joseph C.; Lee, Jan Hau; Latour, Jos M. (Frontiers in Pediatrics, 2024)
Introduction: Literature on parental experiences after childhood critical illness has limited representation from diverse ethnic backgrounds. Parents from global ethnic majority groups have reported worst psychological outcomes and required more social support after childhood critical illness.To explore the experiences of Chinese, Malay, and Indian parents in the first six months after Pediatric Intensive Care Unit (PICU) discharge of their child in Singapore.Methods: Sequential semi-structured qualitative interviews were conducted to collect data from a convenience sample of 28 parents at one month (n=28) and at six months (n=22) after their child's discharge from a multidisciplinary PICU. Framework Analysis was adopted as the qualitative analysis strategy. The PICS-p framework was applied a priori in the Framework Analysis.Findings: Three interdependent domains and seven themes framed the 28 accounts in which ethnically diverse parents reported psychological stressors (PICS-p: emotional health), support received (PICS-p: social health) and practical challenges (transitional health) in the first six months after childhood critical illness. In the emotional health domain, parents were affected by different stressors and had different priorities over their child's survivorship. Only Indian parents reported experiences of stress symptoms, at six months post discharge. Malay parents sought solace from their religion more than Chinese and Indian parents. In the social health domain, parents reported various sources and degree of support received. Familial supports were strong across all groups, while community support was more prominent in Malay as compared to Chinese and Indian parents.A third domain, transitional health, was introduced to capture the difficulties parents faced during the transition from PICU survival to home. Parents from non-Chinese families were more likely to report financial challenges and more involvement of spouses after discharge. Complementary medicine or commercial health products were utilized by Chinese and Malay families.These findings reveal preferred strategies that parents from a global ethnic employ to address the emotional, social and transitional health impacts of their child's critical illness. Future care delivery may consider tailored care plans, communication strategies, and emotional support in PICUs that address the unique ethnic needs of parents during the critical six-months post their child's illness.